Rio x São Paulo : A Copa de 1950 contada através das lutas de representações pela identidade brasileira - Gonçalves de Paiva, Simone; Góis Junior, Edivaldo; Franco Amaral, Silvia Cristina (2019)
This study aimed at observing the struggle for representation of the constitution of a Brazilian identity through soccer, taking into consideration the rivalry between the cities of Rio de Janeiro and São Paulo, which were competing for the control and representation of this identity. In terms of methodology, a historical research was carried out in newspapers with wide circulation in these cities and published in the period between 1949-1950. At the time, they were the most widespread means of communication in the country, that is, they had a larger influence over the public opinion. Thus, this work analyzes how the big media from the two cities represented the Brazilian identity according to their local representations during the event. The conclusion is that the World Cup organization and the Brazilian team's performance were mobilized as discourses that produced symbolic disputes between the two cities, which longed for more power over the production of knowledge and authorized and constituent practices of a "Brasilidade".
O objetivo do estudo foi observar as lutas de representações pela constituição de uma identidade brasileira através do futebol a partir da rivalidade entre as cidades do Rio de Janeiro e São Paulo, que competiam pelo controle e representação dessa identidade. Em termos metodológicos, foi realizada uma pesquisa histórica que teve como fonte jornais de grande circulação das cidades do Rio de Janeiro e São Paulo, publicados no período de 1949-1950, sendo que naquela temporalidade eles eram os meios de comunicação abrangentes, ou seja, tinham destaque na formação de opinião. Assim, o trabalho analisa como a grande imprensa oriunda das duas cidades representava a identidade brasileira de acordo com suas representações regionais mediante à realização do evento. Concluiu-se que a organização da Copa e o desempenho da equipe brasileira eram mobilizados como discursos no sentido de produzir disputas simbólicas entre as duas cidades que almejavam mais poder em relação à produção de saberes e práticas autorizados e constituintes da brasilidade.
Keywords: Soccer; History; World Cup; Press; Futebol^lpt; História; Copa do Mundo; Imprensa